Multi-material NiTi-PEEK hybrid cellular structures by Selective Laser Melting and Hot Pressing: Tribological characterization. (April 2021) - Costa, M.M.; Bartolomeu, F.; Palmeiro, J.; Guimarães, B.; Alves, N.; Miranda, G.; Silva, F.S.
Abstract: In this study, a multi-material NiTi-PEEK cellular structured solution was designed, produced and characterized targeting orthopedic applications. For that purpose, Selective Laser Melting (SLM) technique was used to produce NiTi cellular structures with different open-cell sizes and wall thicknesses. Hot Pressing (HP) technique was used to introduce PEEK in the open-cells of NiTi structures to obtain multi-material components. Morphological characterization showed that the selected SLM processing parameters were suited to achieve high-quality parts without significant defects. Tribological characterization proved an enhanced wear resistance to the multi-material specimens when compared with the mono-material NiTi structures. These multi-material structures are a promising solution for providing a customized stiffness and superior wear resistance to NiTi structures to be integrated in innovative orthopedic designs. Graphical abstract: Image 1 Highlights: NiTi-PEEK multi-material structures were produced by SLM with HP techniques. These structures can provide a customized stiffness and superior wear resistance. Tribological tests were performed for mono and multi-material structures. Wear results revealed an enhanced wear performance for multi-material structures.